Dynamics of SARS-CoV-2 immunity after vaccination and breakthrough infection in rituximab-treated rheumatoid arthritis patients: a prospective cohort study - Kared, Hassen; Jyssum, Ingrid; Alirezaylavasani, Amin; Egner, Ingrid M.; The Tran, Trung; Tietze, Lisa; Lund, Katrine Persgård; Tveter, Anne Therese; Provan, Sella A.; Ørbo, Hilde; Haavardsholm, Espen A.; Vaage, John Torgils; et al. (Frontiers in Immunology, 2024)
Background: SARS-CoV-2 vaccination in rheumatoid arthritis patients (RA) treated with B cell-depleting drugs induced limited seroconversion but robust cellular response. We aimed to document specific T and B cell immunity in response to vaccine booster doses and breakthrough infection (BTI).We included 76 RA treated with rituximab who received up to 4 SARS-CoV-2 vaccine doses or 3 doses plus BTI, in addition to vaccinated healthy donors (HD) and control patients treated with Tumour Necrosis Factor inhibitor (TNFi). We quantified anti-SARS-CoV-2 Receptor-Binding Domain spike (RBD) IgG, anti-Nucleocapsid (NC) IgG, 92 circulating inflammatory proteins, Spike-binding B cells, Spike-specific T cells, and performed high dimensional phenotyping and functional assays. Findings: The time since the last rituximab infusion, persistent inflammation, and age were associated with the anti-SARS-CoV-2 RBD IgG seroconversion. The vaccine-elicited serological response was accompanied by an incomplete induction of peripheral Spikespecific memory B cells but occurred independently of T cell responses. Vaccine-and BTIelicited cellular immunity was similar between RA and HD ex-vivo in terms of frequency or phenotype of Spike-specific cytotoxic T cells and in-vitro in terms of functionality and differentiation profile of Spike-specific T cells. Interpretation: SARS-CoV-2 vaccination in RA can induce persistent effector T-cell responses that are reactivated by BTI. Paused rituximab medication allowed serological response after a booster dose (D4), especially in RA with lower inflammation, enabling efficient humoral and cellular immunity after BTI, and contributed overall to the development of potential durable immunity.